Prognostic value of primary tumor sidedness in patients with non-metastatic IBD related CRC - Is it the exception to the rule? - Kamphues, Carsten; Lefevre, Jeremie H.; Wang, Jane; Amini, Neda; Beaugerie, Laurent; Kuehn, Florian; Park, Sang Hyoung; Andreatos, Nikolaos; Lauscher, Johannes C.; Enea, Diana; Lehmann, Kai S.; Peru, Nicolas; et al. (Surgical oncology, 2022)
Background - Although primary tumor sidedness (PTS) has a known prognostic role in sporadic colorectal cancer (CRC), its role in Inflammatory Bowel Disease related CRC (IBD-CRC) is largely unknown. Thus, we aimed to evaluate the prognostic role of PTS in patients with IBD-CRC. - Methods - All eligible patients with surgically treated, non-metastatic IBD-CRC were retrospectively identified from institutional databases at ten European and Asian academic centers. Long term endpoints included recurrence-free (RFS) and overall survival (OS). Multivariable Cox proportional hazard regression as well as propensity score analyses were performed to evaluate whether PTS was significantly associated with RFS and OS. - Results - A total of 213 patients were included in the analysis, of which 32.4% had right-sided (RS) tumors and 67.6% had left-sided (LS) tumors. PTS was not associated with OS and RFS even on univariable analysis (5-year OS for RS vs LS tumors was 68.0% vs 77.3%, respectively, p = 0.31; 5-year RFS for RS vs LS tumors was 62.8% vs 65.4%, respectively, p = 0.51). Similarly, PTS was not associated with OS and RFS on propensity score matched analysis (5-year OS for RS vs LS tumors was 82.9% vs 91.3%, p = 0.79; 5-year RFS for RS vs LS tumors was 85.1% vs 81.5%, p = 0.69). These results were maintained when OS and RFS were calculated in patients with RS vs LS tumors after excluding patients with rectal tumors (5-year OS for RS vs LS tumors was 68.0% vs 77.2%, respectively, p = 0.38; 5-year RFS for RS vs LS tumors was 62.8% vs 59.2%, respectively, p = 0.98). - Conclusions - In contrast to sporadic CRC, PTS does not appear to have a prognostic role in IBD-CRC.
Online verfügbar: 12 October 2022, Artikelversion: 17 October 2022
Gesehen am 13.06.2023